'… Yo-ho-ho, and a bottle of [beer]!' (R.L. Stevenson) no beer but rather cereal-Food. Commentary: Liu et al. 2018. (December 2019) - Eitam, David
Abstract: Recently, Liu and others have interpreted the Natufian narrow conical mortar cut into a boulder as a storage facility for beer-producing materials. They meticulously studied the residual plant taxa and mortars usewear and carried out experimental studies. We argue that the authors' evidence presented does not necessarily support this interpretation. It, however, reveals direct evidence for the making of cereal-food, namely our suggestion that the Natufian NCM was specially designed for the peeling and milling of barley grains into fine flour for making bread. Highlights: Production of beer in ancient times The invention of bread 2000–3000 years before domestication of cereal Sophisticated agritechnological system The first bread – wild barley flatbread Natufian invention of peeling and milling barley device for making bread